Dosimetry of 177Lu-DOTATOC first circle treatment in patients with advanced metastatic neuroendocrine tumors: A pilot study in China. (January 2022) - Xu, Lei; Meng, Qingle; Yao, Xiaochen; Yang, Rui; Zhang, Pengjun; Li, Rushuai; Wang, Feng
Abstract: First cycle dosimetry calculation of 177 Lu-DOTATOC (single activity:1.59–3.49 GBq) was carried out in eight patients with advanced neuroendocrine tumors (NETs) who underwent whole-body planar (0.5, 24, 48, 72 h) and SPECT/CT scans (24 h). Focal uptake of 177 Lu-DOTATOC was found in primary and metastatic tumors. Organs with the highest absorbed doses per injected activity were tumors (1.293 ± 0.862 mGy/MBq) and spleen (0.461 ± 0.408 mGy/MBq), while low absorbed doses were observed in kidneys (0.384 ± 0.112 mGy/MBq) and bone marrow (0.0297 ± 0.0123 mGy/MBq). 177 Lu-DOTATOC is safe, well-tolerated and appropriate in Chinese NETs patients for PRRT. Highlights: A simplified dosimetry procedure for PRRT is developed in clinical routine with feasibility and repeatability. The absorbed dose was calculated after the first cycle of 177 Lu-DOTATOC treatment in patients with advanced neuroendocrine tumors. Organs with the highest absorbed doses per injected activity were tumors, spleen and kidneys. 177 Lu-DOTATOC dosimetry will lead to personalized therapy and prediction of toxicity in patients with NETs.